Intensive Intervention Improves Outcomes for Chronic Obstructive Pulmonary Disease Patients: A Medical Consortium-Based Management - Shunjin Zhao; Lini Zheng; Maoxian Zhu; Yuexiang Shui; Xuxin Bao; Jun Zhao (Canadian Respiratory Journal)
Chronic obstructive pulmonary disease (COPD) is a major cause of morbidity and mortality. Strategies involving multidimensional approaches for the treatment of COPD are needed. This study aimed to evaluate the efficiency of medical consortium-based management for COPD. Patients were grouped in accordance with whether the hospitals they went to were under the medical consortium. We enrolled 141 COPD patients in the management group and 147 COPD patients in the control group. There was no predetermined sex and disease severity inclusion or exclusion criteria. Patients in the control group were managed by standard care, while patients in the management group were managed with intensive medical intervention jointly by specialists in the hospital and general practitioners and healthcare workers in community health centers. There was no difference in the basal demographics between the two groups. The basal condition of the management group was worse than that of the control group, demonstrated by a higher CAT score and a lower pulmonary function index. Half-year intensive intervention decreased CAT score from 17.28 to 15.62 and the Barthel ADL index from 73 to 60 in the management group, which was associated with better pulmonary rehabilitation, pursed-lip breathing, oxygen usage, and medicine regularity. The benefits became more obvious after one-year intensive intervention in the management group. There was a difference in mMRC grades and smoking cessation between the two groups. This study shows that a one-year intensive intervention improves the patients’ health status and pulmonary function, suggesting that our medical consortium-based management is effective in the treatment of COPD.